Sport Development Index (SDI) di Kabupaten Pacitan - Andri Arif Kustiawan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2020)
The purpose of this study was to identify the level of community participation, the level of physical fitness, and the level of sports development in Pacitan Regency in terms of the community participation index and physical fitness index in 2020. This study uses a quantitative approach with survey research methods and descriptive evaluation approaches. The research sample was Pacitan District Community with a total of 90 people. Data collection techniques with questionnaire techniques (questionnaire) and test techniques. The validity of the measuring instrument used is a standard set in the Sport Development Index (SDI). The results of the study are as follows. (1) The public participation index is 0.388. The community participation index shows that the level of community participation in sports is included in the low category, (2) the community physical fitness index is 0.351. Community physical fitness index shows that public fitness is included in the low category, (3) the level of sports development in terms of participation and physical fitness of the community is included in the low category with an index of 0.369. Conclusions, participation index, physical fitness, and sports development in Pacitan District are included in the low category. Keywords: Sport Development Index, Community Participation, Physical Fitness